Investigation of Ferroelectric Polymer Langmuir Film Properties. Issue 1790 (2015) - Reece, Timothy J.; Behn, Wyatt A.; Sanabria-Díaz, Adrián
ABSTRACT: Thin films of Polyvinylidene Fluoride (PVDF) copolymers have been incorporated within ferroelectric field effect transistors, all organic thin film transistor devices (OTFTs), piezoelectric actuators, and recently proposed as the ferroelectric layer in a promising multiferroic tunnel junction configuration [1]. The properties of most of these devices would benefit from reduced thickness and better thickness control of the ferroelectric layer during device processing. A proven means for fabricating ultrathin films of the PVDF copolymer is the Langmuir-Blodgett (LB) technique. This technique involves dissolving the polymer in a volatile solvent which is then dispersed dropwise onto a purified water subphase, leaving an ultrathin layer of the copolymer on the water surface. The ability to control the thickness on the molecular level is the most prominent feature of this technique. In some early studies [2], the minimum thickness of these films was found to be about 5 Angstroms, or roughly the same thickness as the intermolecular spacing of the all-trans β phase for the ferroelectric polymers. Later studies have led to the fabrication of films composed of thicker transfer steps: ∼ 1.8 nm per deposition [3]. The discrepancy is likely explained by the nature of the VDF molecule: it is not an amphiphile. In this study, we further investigate the properties of Langmuir films of ferroelectric copolymers and discuss the observation of an apparent monolayer phase transition based on abrupt changes observed in the compressibility of the films. The main goal of this project is to discover the extent to which the device properties (like transfer step thickness) of PVDF films can be modified through processing conditions.